2022
DOI: 10.1111/add.16025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 10 add‐on HF‐rTMS treatment sessions on alcohol use and craving among detoxified inpatients with alcohol use disorder: a randomized sham‐controlled clinical trial

Abstract: Background and aims Alcohol use disorder (AUD) is a chronic disorder with high relapse rates. There are currently few clinical trials of high frequency repetitive transcranial magnetic stimulation (HF‐rTMS) to reduce alcohol use among AUD patients, and results are mixed. The current study tested the effect of 10 add‐on sessions of HF‐rTMS over the right dorsolateral pre‐frontal cortex (DLPFC) on alcohol use and craving. Design Single‐center, single blind sham‐controlled parallel‐group RCT (n = 80), with 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 79 publications
0
2
0
1
Order By: Relevance
“… 10 Active OR 10 Sham Sessions Left DLPFC 110% 20 Hz Figure-8 Coil Craving Active vs. Sham: −2.22 [−2.99 – −1.45] Consumption Active vs. Sham: −1.84 [−2.57 – −1.12] NA Active rTMS significantly ↓ days of heavy drinking and alcohol craving compared to sham. Hoven et al [ 70 ] N = 80 A randomized, dingle-blind, sham-controlled study with recently abstinent, alcohol-dependent participants. 10 Active OR 10 Sham Sessions Right DLPFC 110% 10 Hz Figure-8 Coil Craving Active vs. Sham: −0.16 [−0.59–0.28] NA Abstinent Days Over 6-months Active vs. Sham: −0.13 [−0.56–0.30] No significant difference in number of abstinent days over 6-months or alcohol craving was observed following active rTMS compared to sham stimulation.…”
Section: Methodsmentioning
confidence: 99%
“… 10 Active OR 10 Sham Sessions Left DLPFC 110% 20 Hz Figure-8 Coil Craving Active vs. Sham: −2.22 [−2.99 – −1.45] Consumption Active vs. Sham: −1.84 [−2.57 – −1.12] NA Active rTMS significantly ↓ days of heavy drinking and alcohol craving compared to sham. Hoven et al [ 70 ] N = 80 A randomized, dingle-blind, sham-controlled study with recently abstinent, alcohol-dependent participants. 10 Active OR 10 Sham Sessions Right DLPFC 110% 10 Hz Figure-8 Coil Craving Active vs. Sham: −0.16 [−0.59–0.28] NA Abstinent Days Over 6-months Active vs. Sham: −0.13 [−0.56–0.30] No significant difference in number of abstinent days over 6-months or alcohol craving was observed following active rTMS compared to sham stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…A few years later, in 2015, Mishra et al [18] showed that stimulation on the left side (using the same protocol) had comparable efficacy to that on the right side. In 2022 Hoven et al [19] used a very similar protocol, also stimulating the right dorsolateral prefrontal cortex. The study included a slightly larger group of subjects.…”
Section: Methodsmentioning
confidence: 99%
“…W 2022 roku Hoven i wsp. [19] zastosowali bardzo podobny protokół, również stymulując prawą grzbietowo boczną korę przedczołową. Badaniem objęto nieco większą grupę osób.…”
Section: Wyszukanieunclassified